LEARNERS LEVEL OF SATISFACTION ON SCHOOL RELATED FACTRS AND ITS EFFECT ON ACADEMIC PERFORMANCE - SAGARIO, ARJAY; BINONDO, ROBERT JR.; DALIPE, ANGELIE; GUTIERREZ, RONALD JHON; BATANG, JONARD (International Journal of Arts, Sciences and Education, 2023)
The purpose of this study was to examine the connection between students’ academic achievement and their satisfaction with the educational opportunities provided by their school. The study employed a descriptive correlational research design and surveyed 307 St. Anthony’s College of Sta. Ana, Cagayan Inc. respondents from various departments, including Elementary, Junior High School and Senior High School. Students were satisfied with the school-related resources available to them, including student-centeredness, instructional effectiveness, campus support, safety and security, academic advising/ counselling effectiveness and admissions and financial aid effectiveness. The study emphasized that a school’s provision of a safe and conducive environment for learning, as well as high-quality education, is essential for achieving its primary goal. In addition, the study highlighted the importance of identifying the variables that contribute to students’ satisfaction with their educational experiences, as this is essential for successfully recruiting students. The short-term student satisfaction attitude that results from evaluating an institution’s educational experience, services, and facilities was also discussed. By determining the extent to which students are satisfied with the various components of the schools can gain valuable insights for enhancing the quality of services they offer, according to the studies’ findings. Findings indicate that prioritizing student’s needs is crucial, as meeting these needs allows them to develop into well-rounded people. KEYWORDS: students’ satisfaction, basic education department, academic performance, student-centeredness, instructional effectiveness, campus support, safety and security, academic advising, admission, financial aid effectiveness.